Les amphores du nord-est de la Gaule (Territoire français.) Contribution à l'histoire de l'économie provinciale sous l'Empire romain - Baudoux, Juliette (Documents d'archéologie française, 1996)
Shirting front a systematic study of Roman amphora discovered at approximately one hundred sites in the north-east of Gaul, this research treats certain aspects of provincial economic history, regarding impart and consumption of foods under the Roman Empire in the region, which, in Antiquity, was strategically situated on an important crossroad, the joining of the Rhône corridor with the "Germanic limes". The original aspects are tested through the analysis of the morphology, epigraphy and macroscopic description of the clay material of these recipients. The observation of the differences in distribution helps us to understand the directions of economic currents over lime and specific consumer habits whether in urban or rural areas.